Modelling drag forces on a wheelchair racing simulator - Bayat, A.; Chénier, F. (Proceedings of the 11th International Conference on Sport Sciences Research and Technology Support icSPORTS - Volume 1, 2023)
A racing wheelchair simulator is a stationary device that allows para-athletes to train inside, in different simulated conditions (e.g., rolling resistance, wind). Apart from improving performance during training sessions, it also allows researchers to study the biomechanics of the propulsion in a laboratory, which is important because wheelchair racing can cause musculoskeletal disorders and pain in athletes. For these reasons, the realism of these simulators is paramount, and having a model that reproduces a non-linear relationship between drag force, wheeling speed and wind speed is one of the criteria for achieving this realism. In this work, we develop and characterize such a model through empirical data recorded on a racing track, and then implement it on a racing wheelchair simulator with a haptic controller. Propelling on this simulator proved to be somewhat less challenging than real-life conditions, with a measured resistance force approximately 5 N lower than during real p ropulsion conditions. However, the resistance expectedly increased as simulated face wind increased. These results show a promising avenue for racing wheelchair athletes, both for training and assessing/correcting their biomechanics.